Common African pests and diseases of cassava, yam, sweet potato and cocoyam - Theberge, R.L. (1994)
The common fungal and bacterial diseases and arthropod and nematode pests associated with the cultivation of cassava [Manihot esculenta], yam [Dioscorea sp.], sweet potato [Ipomoea batatas] and cocoyam [taro] in Africa are described. The publication is illustrated with many colour photographs and is intended as a guide for growers in order to help identify production constraints. For each of the diseases and nematode pests, information is provided on common names, range, host plants, symptom of damage, spread and losses caused. For the arthropod pests, information is provided on common names, distribution, host plants, morphology, symptoms of damage, biology and pest status. Brief methods for the control of the arthropod pests and nematodes are outlined.